Iran and Russia on the path to building a comprehensive, principled partnership - V. I. Belov; D. M. Ranjbar (Informaciâ i Innovacii)
The article deals with the main provisions of the Treaty on the Comprehensive Strategic Partnership between the Islamic Republic of Iran and the Russian Federation of 17 January 2025. The study examines the historical context, legal foundations, and strategic implications of the treaty, which marks a new era in bilateral relations. The agreement, signed by Presidents Vladimir Putin and Masoud Pezeshkian, outlines a 20-year framework for cooperation in various domains, including security, defense, economy, energy, and regional stability. The research methodology involves a qualitative analysis of treaty provisions and their alignment with previous agreements between the two nations, such as the 1921 Treaty between Persia and USSR and the 2001 Treaty on the Fundamentals of Relations. The study also incorporates geopolitical and economic evaluations to assess the treaty's potential impact. The results highlight that the treaty establishes a strong legal foundation for cooperation, enhancing military and technical collaboration, promoting trade and economic partnerships, and reinforcing mutual non-interference principles. A significant emphasis is placed on energy projects, including oil, gas, and nuclear initiatives, as well as the development of the International North–South Transport Corridor. Additionally, the agreement outlines cooperative mechanisms for countering unilateral sanctions and advancing multipolar international governance. The treaty signifies a strategic shift in Eurasian geopolitics, positioning Iran and Russia as key allies in regional security and economic integration. The findings suggest that this agreement will likely have long-term implications for international relations, particularly in Central Asia, the Middle East, and the broader Eurasia.